Hepatitis C virus genotype distribution in Turkey remains unchanged after a decade: Performance of phylogenetic analysis of the NS5B, E1, and 5’UTR regions in genotyping efficiency - Kabakçı Alagöz, Gökçe; Karataylı, Senem Ceren; Karataylı, Ersin; Çelik, Esra; Keskin, Onur; Dinç, Bedia; Çınar, Kubilay; İdilman, Ramazan and Yurdaydın, Cihan and Bozdayı, A. Mithat (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: Hepatitis C virus (HCV) genotyping has a considerable effect on therapy. The aim was to determine the change in prevalence of HCV genotypes in Turkey during the last decade and to compare the performance of DNA sequencing of different targets in the HCV genome (NS5B, E1, and 5’UTR). Materials and Methods: Five hundred HCV RNA-positive patients (226 males, 274 females) were included in the study. The NS5B, E1, and 5’UTR regions of the HCV genome were amplified by polymerase chain reaction (PCR) in patients where possible. Amplified PCR products were sequenced directly, and phylogenetic analysis was performed. A commonly used database, namely www.hcv.lanl.gov, was also used to determine the genotypes. Results: Phylogenetic analysis of the NS5B, E1, and 5’UTR regions showed that 1b was the most frequent genotype, with percentages of 92.5%, 93.5%, and 87.7%, respectively. Genotype 1a was the second most prevalent genotype, with ratios of 6.7%, 5.6%, and 6.6%, whereas genotype 2a was detected in proportions of 0.4%, 0.2%, and 0.8%, respectively. Genotype 5 or 6 was not detected among patients. The phylogenetic analysis showed discordant results with 18 patients’ genotypes for different targets. The phylogenetic analysis showed similar results with the hcv.lanl. gov database for the E1 and NS5B sequences. Conclusion: There has been no change in genotyping profiles of Turkey during the last decade, representing 1b as the most prevalent subtype, followed by 1a. Phylogenetic analysis of HCV indicated high performance compared with the hcv.lanl.gov database when sequences of E1 and NS5B regions were analyzed.